Pengaruh Kesehatan Mental Terhadap Employee Engagement dan Kinerja (Studi Dinas Pemuda Olahraga dan Pariwisata) - Radiyah Auliyah; Muhammad Kasran; Haedar Haedar (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The study aims to determine the Effect of Mental Health on Employee Engagement and Performance (Study of the Youth, Sports, and Tourism Office). The method used in this study is a correlational quantitative method carried out using 42 employees and staff of the Youth, Sports, and Tourism Office of North Luwu Regency. The research sampling technique uses a questionnaire and also uses SPSS Version 30 in processing the research data. These results indicate that Mental Health (X) simultaneously has a positive and significant effect on Employee Engagement (Y1) and Performance (Y2). And Employee Engagement (Y1) also has a positive and significant effect on Performance (Y2). In addition, Mental Health (X) has an indirect effect on Performance (Y2) but through Employee Engagement (Y1) as a partial mediator. This means that Mental Health not only increases employee engagement to work and the Organization, but also contributes to improving overall Performance. In addition, employee engagement has also been shown to have a significant effect on improving employee performance. Indirectly, mental health also improves performance through employee engagement. The better the mental health, the higher the employee engagement and performance, which ultimately has a positive impact on the organization as a whole.